A 'Rosetta Stone' for Protoplanetary Disks: The Synergy of Multi-Wavelength Observations. (2016) - Sicilia-Aguilar, A.; Banzatti, A.; Carmona, A.; Stolker, T.; Kama, M.; Mendigutía, I.; Garufi, A.; Flaherty, K.; van der Marel, N.; Greaves, J.
Abstract: Recent progress in telescope development has brought us different ways to observe protoplanetary disks: interferometers, space missions, adaptive optics, polarimetry, and time- and spectrally-resolved data. While the new facilities have changed the way we can tackle open problems in disk structure and evolution, there is a substantial lack of interconnection between different observing communities. Here, we explore the complementarity of some of the state-of-the-art observing techniques, and how they can be brought together to understand disk dispersal and planet formation. This paper was born at the 'Protoplanetary Discussions' meeting in Edinburgh, 2016. Its goal is to clarify where multi-wavelength observations converge in unveiling disk structure and evolution, and where they challenge our current understanding. We discuss caveats that should be considered when linking results from different observations, or when drawing conclusions from limited datasets (in terms of wavelength or sample). We focus on disk properties that are currently being revolutionized, specifically: the inner disk radius, holes and gaps and their link to large-scale disk structures, the disk mass, and the accretion rate. We discuss how their connections and apparent contradictions can help us to disentangle the disk physics and to learn about disk evolution.